The Development of Stick and Ball Sports on Gateball (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research is to make product design development of stick and ball sports in gateball. The approach used in this study is a method of Research and Development. The subject of this research is the Central Java on gateball club event gateball in Semarang and Yogyakarta. Experts and expert expert gateball expert in mechanical engineering. The data analysis phase the work field, and the data analysis stage include observation, observation, interviews, and documentation of the test kefektifan products, expert judgment expert expert gateball and expert mechanical engineering expert. The results of this research are stick and ball exercise for beginner players gateball gateball. The result of the validator 3 expert expert from the expert gateball and expert mechanical engineering product validation data beginning the first phase obtained a score above 73 definitions of the criteria of â€œgoodâ€, on the second stage of the product validation data obtained a score above the 81 criteria for â€œexcellentâ€. The results of the interviews to the development of gateball players 19 stick and ball gateball can not be used to play in a match and can be used for subsequent exercises but for beginners a product development tool model stick and ball gateball â€œ INC. â€œcan be used to enhance the ability of basic techniques in motion game for players, gateball.